2016
DOI: 10.1002/hed.24393
|View full text |Cite
|
Sign up to set email alerts
|

BRAF V600E detection in cytological thyroid samples: A key component of the decision tree for surgical treatment of papillary thyroid carcinoma

Abstract: The preoperative knowledge of the V600E mutation status is fundamental to plan total thyroidectomy with certainty and should be part of the decision tree for the management of thyroid nodules. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1017-1021, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(42 reference statements)
0
6
1
Order By: Relevance
“…Therefore, BRAF mutation detection can influence the treatment strategy and surgical plan of the nodule that cannot definitively fit into a BSRTC category. Studies have suggested that patients with preoperative confirmation of BRAF V600E should undergo total thyroidectomy, regardless of whether the FNAC is malignant or suspected of malignancy 34 . Based on the current study, we have not yet reached this conclusion.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Therefore, BRAF mutation detection can influence the treatment strategy and surgical plan of the nodule that cannot definitively fit into a BSRTC category. Studies have suggested that patients with preoperative confirmation of BRAF V600E should undergo total thyroidectomy, regardless of whether the FNAC is malignant or suspected of malignancy 34 . Based on the current study, we have not yet reached this conclusion.…”
Section: Discussioncontrasting
confidence: 69%
“…Studies have suggested that patients with preoperative confirmation of BRAF V600E should undergo total thyroidectomy, regardless of whether the FNAC is malignant or suspected of malignancy. 34 Based on the current study, we have not yet reached this conclusion.…”
Section: Discussionmentioning
confidence: 59%
“…Currently, fine needle aspiration biopsy (FNAB) is the first choice for the preoperative diagnosis of multifocality with an acceptable accuracy, since it is even effective on the treatment of the tumour foci with a diameter of 5 mm or less [37]. Although whether BRAF V600E analysis could be routinely used in clinical practice is still controversial, it has been proved to be feasible preoperatively [38]. Moreover, a system meta-analysis has proved that preoperative BRAF V600E test can improve the diagnostic accuracy of FNAB [39].…”
Section: Discussionmentioning
confidence: 99%
“…[2] It is well-known for its usually mild clinical course among the cancers with a very high 10-year survival rate (>90%). [6][7][8] However, the recurrence rate has been reported to range between 20% and 30% especially in the neck lymph nodes. [9,10] Thus, the early diagnosis of PTC is vital.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The overall prognosis of PTC is good with a 10-year survival rate of >90%. [6][7][8] However, the recurrence rate has been reported to range from 20% to 30% especially in the neck lymph nodes. [9,10] The early diagnosis and management of PTC continued remaining a priority.…”
Section: Introductionmentioning
confidence: 99%